Role of Animal Models to Advance Research of Bacterial Osteomyelitis - Billings, Caroline; Anderson, David E. (Frontiers in Veterinary Science, 2022)
Osteomyelitis is an inflammatory bone disease caused by pyogenic microorganisms, typically bacteria, which causes progressive bone destruction and loss. The most common bacteria associated with chronic osteomyelitis is Staphylococcus aureus. The incidence of osteomyelitis in the United States is estimated to be upwards of 50,000 cases annually and places a significant burden upon the healthcare system. There are three general categories of osteomyelitis: hematogenous; secondary to spread from a contiguous focus of infection, often from trauma or implanted medical devices and materials; and secondary to vascular disease, often a result of diabetic foot ulcers. Independent of the route of infection, osteomyelitis is often challenging to diagnose and treat, and the effect on the patient’s quality of life is significant. Therapy for osteomyelitis varies based on category and clinical variables in each case. Therapeutic decisions are typically reliant upon protracted antimicrobial therapy and surgical interventions. Therapy is most successful when intensive and initiated early, although infection may recur months to years later. Also, treatment is accompanied by risks such as systemic toxicity, selection for antimicrobial drug resistance (AMR) from prolonged antimicrobial use, and loss of form or function of the affected area due to radical surgical debridement or implant removal. The challenges of diagnosis and successful treatment, as well as the negative impacts on patient’s quality of life, exemplify the need for improved strategies to combat bacterial osteomyelitis. There are many in vitro and in vivo investigations aimed towards better understanding of the pathophysiology of bacterial osteomyelitis, as well as improved diagnostic and therapeutic strategies. Here, we review the role of animal models utilized for the study of bacterial osteomyelitis and their critically important role in understanding and improving the management of bacterial osteomyelitis.